The Portrait of Islamic Arab Descendant Community in Maintaining Identity and Diversity in Bali - Fatiyah, Fatiyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
The existence of a Muslim community of Arab descent in Bali has existed since Bali was still a kingdom. The existence of this community as an ethnic and religious minority does not exclude it from Balinese Hindu culture. It still exists with distinctive physical and cultural characteristics. The purpose of this research is to describe and analyze the existence, implementation of religious and cultural rituals, as well as the role of Arab descendants in maintaining inter-religious harmony in Bali. This research uses a qualitative approach. Data collection through: in-depth interviews, observation, and documentation. Data is processed and analyzed using interactive qualitative analysis techniques. Research findings: First, that the Muslim minority of Arab descent in Bali has an existence to this day, namely by its existence inhabiting areas called “Arab Villages”. Apart from that, some families also dispersed to areas outside Arab Village as a form of survival. Its existence can also be seen from the ancestral culture that is still maintained, especially in religious celebrations. Second, as a minority community with identification as Muslims, they continue to maintain religious rituals as devout Muslims. They are also active in holding family recitations as gatherings between extended families. Apart from that, ancestral cultures such as Arabic dialect are still used in internal family conversations. Third, as a minority community, the Arab community in Bali actively tries to identify themselves as Balinese. The Arab community in Bali is an inclusive community. They actively blend into Balinese society which reflects it as a tolerant society. Those phenomena can be used as reference material in realizing a harmonious life in a pluralistic society and in responding to negative attitudes or views regarding Islam and Arab descendants today, due to differences in political views as well. الملخص كان وجود مجتمع مسلم من أصل عربي في بالي موجودًا منذ أن كانت بالي لا تزال مملكة. إن وجود هذا المجتمع كأقلية عرقية ودينية لا يستبعد هذا المجتمع من الثقافة الهندوسية البالية. ولا تزال موجودة بخصائص مادية وثقافية مميزة.الغرض من كتابة هذا المقال هو وصف وتحليل وجود وتنفيذ الطقوس الدينية والثقافية، فضلا عن دور المنحدرين من العرب في الحفاظ على الانسجام بين الأديان في بالي. يستخدم هذا البحث نهجا نوعيا. جمع البيانات من خلال: المقابلات المتعمقة، والملاحظة، والتوثيق. تتم معالجة البيانات وتحليلها باستخدام تقنيات التحليل النوعي التفاعلية. نتائج البحث: أولاً، أن الأقلية المسلمة ذات الأصول العربية في بالي لها وجود حتى يومنا هذا، وذلك من خلال تواجدها في مناطق تسمى